Development and evaluation of electrochemical glucose enzyme biosensors based on carbon film electrodes - Florescu, Monica (2005)
Electrochemical glucose enzyme biosensors have been prepared on carbon film electrodes made from carbon film electrical resistors. Evaluation and characterisation of these electrodes in phosphate buffer saline solution has been carried out with and without pretreatment by cycling in perchloric acid or at fixed applied potential. Both pretreatments led to a reduction in the carbon surface oxidation peak and enabled better detection of hydrogen peroxide in the pH range of 5-7. Glucose oxidase enzyme was immobilised on the carbon surface by mixing with glutaraldehyde, bovine serum albumin and with and without Nafion. The performance of these two types of electrode was similar, that containing Nafion being more physically robust. Linear ranges were up to around 1.5 mM, with detection limits 60 [mu]M, and pretreatment of the carbon film electrode at a fixed potential of +0.9 V versus SCE for 5 min was found to be the most beneficial. Michaelis-Menten constants between 5 mM and 10 mM were found under the different experimental conditions. Coating the immobilised enzyme layer with a thin layer of Nafion was found to give similar results in the determination of glucose to mixing it but with benefits against interferences for the analysis of complex matrices, such as wine. Potentialities, for a short-term-use or disposable sensors, are indicated.